2008
DOI: 10.1017/s0007114508055669
|View full text |Cite
|
Sign up to set email alerts
|

Impact of energy deficit calculated by a predictive method on outcome in medical patients requiring prolonged acute mechanical ventilation

Abstract: To assess energy balance in very sick medical patients requiring prolonged acute mechanical ventilation and its possible impact on outcome, we conducted an observational study of the first 14 d of intensive care unit (ICU) stay in thirty-eight consecutive adult patients intubated at least 7 d. Exclusive enteral nutrition (EN) was started within 24 h of ICU admission and progressively increased, in absence of gastrointestinal intolerance, to the recommended energy of 125·5 kJ/kg per d. Calculated energy balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(107 citation statements)
references
References 55 publications
5
90
0
12
Order By: Relevance
“…In contrast, previous observation al studies suggested a better outcome with increased caloric and protein intake owing to the early supplemental or pre dominant use of PN in critically ill pa tients [1,10,13,27,32,35]. In the major ity of these studies, only a limited num ber of severely septic patients were includ ed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, previous observation al studies suggested a better outcome with increased caloric and protein intake owing to the early supplemental or pre dominant use of PN in critically ill pa tients [1,10,13,27,32,35]. In the major ity of these studies, only a limited num ber of severely septic patients were includ ed.…”
Section: Discussionmentioning
confidence: 93%
“…The advantage of the one nutrition type is thereby regarded as the disadvantage of the other, as both have inherent risks of under or overfeed ing. On the one hand, large energy deficits resulting from a low caloric intake dur ing EN may lead to increased infectious complications and a longer intensive care unit (ICU) stay [10,13,35]. On the other hand, PN is associated with nutritional ex cess leading to hyperglycemia, increased meta bolic stress, and infectious morbi dity [9,28].…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative energy deficits are associated with loss of muscle mass, poor wound healing, increased risk of infections, increased morbidity, and a higher risk of mortality in critically ill adults (24,25). Both energy and protein deficits are undesirable.…”
Section: Energy Imbalance During Chronic Illness and Its Impact On Oumentioning
confidence: 99%
“…O estudo de Faisy et al 25 demonstrou uma associação entre o balanço energético negativo e a mortalidade em UTI de pacientes gravemente doentes que permaneceram por tempo prolongado sob VM enquanto recebiam nutrição enteral exclusiva. No estudo realizado por Kan et al 10 , os pacientes que receberam uma alimentação inadequada para suprir a demanda energética dependeram por mais tempo da VM.…”
Section: I S C U S S ã Ounclassified